2016
DOI: 10.4049/jimmunol.1502438
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of NKG2C Copy Number with the Distribution of Distinct Cytomegalovirus-Induced Adaptive NK Cell Subsets

Abstract: CD94/NKG2C and lack of FcεRγ (FcRγ) expression are considered markers of the adaptive NK cell response to human CMV (HCMV) infection. Despite the fact that FcRγ− and NKG2Cbright NK cells share some phenotypic, epigenetic, and functional features, their relationship remains unclear. To address this issue, a systematic analysis of NKG2Cbright and FcRγ expression was carried out in NK cells from a cohort of healthy young adults (n = 81) considering NKG2C copy number, previously related to the magnitude of NKG2C+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
77
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 44 publications
14
77
1
Order By: Relevance
“…HCMV‐adapted NK cells lacking NKG2C expression were also reported, most of them expressing activating KIRs 160, 161. Using a large NKG2C‐deficient cohort, it was recently demonstrated that adaptive NK cell responses could occur in the absence of both activating KIRs and NKG2C; however, these adaptive NK cells also largely display repertoire deviation toward self‐specific inhibitory KIR expression 162, 163. Also, self‐specific inhibitory KIR expression is not required for generating adaptive NK cells but is probably necessary for optimal functions.…”
Section: Kir Gene Expressionmentioning
confidence: 99%
“…HCMV‐adapted NK cells lacking NKG2C expression were also reported, most of them expressing activating KIRs 160, 161. Using a large NKG2C‐deficient cohort, it was recently demonstrated that adaptive NK cell responses could occur in the absence of both activating KIRs and NKG2C; however, these adaptive NK cells also largely display repertoire deviation toward self‐specific inhibitory KIR expression 162, 163. Also, self‐specific inhibitory KIR expression is not required for generating adaptive NK cells but is probably necessary for optimal functions.…”
Section: Kir Gene Expressionmentioning
confidence: 99%
“…Interestingly, infections not only activate NK cells but also shape NK cell functions (5254). Thus, cytomegalovirus (CMV) induces expansion of NK cells that produce IL-10 in mice, to prevent excess of activation of CD8 T cells (55, 56).…”
Section: Possible Role Of Nk Cells In Ms and Its Animal Modelmentioning
confidence: 99%
“…Similarly to MCMV, human cytomegalovirus (HCMV) is able to induce the expansion of a NK subpopulation expressing the CD94/NKG2C activating receptor [57, 58]. The expansion of CD94/NKG2C + NK cells is believed to be linked to the recognition of a ligand on HCMV infected cells [59], but unlike in the mouse, this ligand has not been identified yet (Figure 3(a)). Surprisingly, this CD56 dim /CD16 bright /NKG2C + cell subset does not perform a specific cytotoxicity against fibroblasts infected with HCMV, as expected from memory cells.…”
Section: Memory-like Nk Cells In Viral Infectionsmentioning
confidence: 99%
“…Surprisingly, this CD56 dim /CD16 bright /NKG2C + cell subset does not perform a specific cytotoxicity against fibroblasts infected with HCMV, as expected from memory cells. Nevertheless, when stimulated by opsonized HCMV + target cells via CD16 receptor, CD56 dim /CD16 bright /NKG2C + cells display an enhanced ability to proliferate [60] and to secrete cytokines (in particular TNF-alpha) [59, 61]. Notably, humans lacking one KLRC2 allele that encodes NKG2C receptor had a compromised NK cell differentiation during HCMV infection, with altered adaptive response and high anti-HCMV IgG titers [62, 63].…”
Section: Memory-like Nk Cells In Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation